Nanopartículas de alginato como sistema de liberação para o herbicida clomazone - Silva, Mariana dos Santos [UNESP]; Cocenza, Daniela Sgarbi [UNESP]; Melo, Nathalie Ferreira Silva de [UNESP]; Grillo, Renato [UNESP]; Rosa, André Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Sociedade Brasileira de Química, 2010)
In this paper, we describe the preparation of alginate nanoparticles as a delivery system for the herbicide clomazone. Two different methods were investigated and characterized by size distribution, zeta potencial, pH and in vitro release. The alginate/AOT nanoparticles had higher rates of association of the herbicide clomazone than alginate/chitosan nanoparticles. Clomazone release profile, showed a significant difference in release behavior of pure herbicide in solution when compared with herbicide loaded in both alginate nanoparticles. This study is important to construct a biodegradable release system using herbicide for later release into more specific targets, avoiding contamination of environmental matrices.
Alginate nanoparticles as a controlled release system for clomazone herbicide
Keywords: environmental chemistry; herbicide; alginate nanoparticles